FIB Plan and Side View Cross-Sectional TEM Sample Preparation of Nanostructures. (13th November 2013) - Lenrick, Filip; Ek, Martin; Jacobsson, Daniel; Borgström, Magnus T.; Wallenberg, L. Reine
Abstract Focused ion beam is a powerful method for cross-sectional transmission electron microscope sample preparation due to being site specific and not limited to certain materials. It has, however, been difficult to apply to many nanostructured materials as they are prone to damage due to extending from the surface. Here we show methods for focused ion beam sample preparation for transmission electron microscopy analysis of such materials, demonstrated on GaAs–GaInP core shell nanowires. We use polymer resin as support and protection and are able to produce cross-sections both perpendicular to and parallel with the substrate surface with minimal damage. Consequently, nanowires grown perpendicular to the substrates could be imaged both in plan and side view, including the nanowire–substrate interface in the latter case. Using the methods presented here we could analyze the faceting and homogeneity of hundreds of adjacent nanowires in a single lamella.